CAPWAP protocol and context transfer to support seamless handover - M. Hasnan, Siti Norhaizum; Ayu, Media Anugerah; Mantoro, Teddy; Mazlan, M. Hasbullah; Abobakr, M.; Balfaqih, A.; Haseeb, Shariq (Springer Berlin Heidelberg, 2013)
Nowadays, real-time applications become immensely popular and available over wireless devices. An emerging technology IEEE 802.11 Wireless Local Area Network (WLAN) has brought users to have trendy gadgets like smart phones, tablets and laptops. These applications require a fast and efficient handover that guarantee a service of security and Quality of Service (QoS). However, the users will face disruption which can cause high transition delay while running multimedia services. This paper presents an overview of Control and Provisioning Wireless Access Point (CAPWAP) protocol; a solution to overcome security problem during handover within a large network. Furthermore, we conducted a survey in this paper in order to find an algorithm that can support seamless handover in centralized architecture. Overall, the paper ends with further work by suggesting a design of CAPWAP protocol using predictive context transfer in centralized architecture.